SISTEM PENDIDIKAN YANG HIDUP: TELAAH HAKIKAT,MEKANISME PENGENDALIAN, DAN PEMELIHARAAN KUALITAS PESERTA DIDIKDI MTSN BINJAI - Makmur Syukri; Firmansyah Firmansyah; Muhammad Salim El Taufiq (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the essence of the living educational system, the mechanisms for controlling students' quality, and the strategies for maintaining and improving students' quality at MTsN Binjai. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and document analysis involving the principal, vice principals, teachers, guidance and counseling teachers, students, and parents. Data were analyzed using interactive techniques, including data reduction, data display, and conclusion drawing, while trustworthiness was ensured through source and technique triangulation. The findings indicate that the living educational system is developed through the integration of Islamic values, madrasah culture, leadership, learning processes, and active stakeholder participation. Student quality control is implemented through academic evaluation, character development, behavioral supervision, counseling services, and collaboration with parents. Students' quality is maintained and improved by strengthening religious culture, enhancing academic and non-academic potential, and fostering partnerships among the madrasah, families, and the community. The novelty of this study is the development of the living educational system as a holistic, adaptive, and sustainable educational ecosystem model for improving students' quality in the madrasah context.